2020
DOI: 10.1016/j.jebo.2018.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral motivations for self-insurance under different disaster risk insurance schemes

Abstract: This paper presents a lab-in-the-field experiment with 2111 Dutch homeowners in floodplain areas to examine the impacts of financial incentives and behavioral motivations for self-insurance under different flood insurance schemes. We experimentally varied the insurance type (mandatory public versus voluntary private) and the availability of a premium discount incentive for investing in flood damage mitigation measures. This setup allowed us to examine the existence of moral hazard, advantageous selection and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 82 publications
2
38
1
2
Order By: Relevance
“…Another study which was done among Florida households finds a positive correlation between insurance coverage and private mitigation measures [22]. Similarly, a recent study that uses an experiment among Dutch homeowners finds that individuals who buy insurance are more likely to selfprotect against flooding [23].…”
Section: Introductionmentioning
confidence: 94%
“…Another study which was done among Florida households finds a positive correlation between insurance coverage and private mitigation measures [22]. Similarly, a recent study that uses an experiment among Dutch homeowners finds that individuals who buy insurance are more likely to selfprotect against flooding [23].…”
Section: Introductionmentioning
confidence: 94%
“…For instance, in countries where the government can provide compensation for flood damage, such as the Netherlands, individual investments in reducing flood damage save tax money for compensated victims after flood events. In a previous survey with Dutch homeowners, we elicited social norms with regard to individual flood damage-reducing measures (Mol et al, 2020b). We found that 25% of Dutch homeowners think that their peers would approve if they invested in damage-reducing measures, 50% are indifferent, and the remaining 25% think that their peers would disapprove.…”
Section: Introductionmentioning
confidence: 93%
“…Persepsi bahwa investasi pada mitigasi merupakan tindakan yang efektif, menyebabkan adanya minat yang tinggi terhadap asuransi banjir di Dutch (Mol et al, 2018). Sebaliknya, dengan adanya persepsi rendahnya kemungkinan terjadinya banjir menyebabkan kurangnya keinginan dalam pembelian asuransi di Belanda (Botzen & Van den Bergh, 2012).…”
Section: Pendahuluanunclassified